Effects of AMF inoculation on accumulation of plant-soil nutrients and colonization of native DSE in eastern grassland opencast mining area - Linlin XIE; Yinli BI; Tao LIU (Meitan xuebao)
Different grasses in the eastern steppe have different proportions of living space, so the study on the relationship between the growth and competition of the grassland grasses is of great significance to reveal the 1ecological evolution of the grassland. According to the current situation of the habitat and the dump in the Shengli opencast mining area in Xilinhot, Inner Mongolia, different plant ratios combined with microbial inoculation were used to investigate the effect of plant-fungus combination on the soil improvement and vegetation restoration in the dump and screen the best planting mode suitable for the ecological restoration in the dump. The selection of suitable fungi is an important prerequisite for the ecological remediation of mining areas. To verify the ecological effect of arbuscular mycorrhiza fungi (AMF), the comprehensive restoration of plant and microbial (AMF) in the dump of the Shengli coal mining area was investigated. Results showed that the dominant factors affecting soil and plants were planting patterns and AMF inoculation, respectively. The comprehensive influence of soil and plant indicators was as follows: AMF inoculation > plants planting. Therefore, adding appropriate microbial agents would actively improve the remediation efficiency in the dump of mining area. The weight ratio of Leguminosae∶Poaceae = 1∶3 + AMF planting mode could promote soil improvement, accelerate the accumulation of soil nutrients, and promote plant growth and nutrient absorption, which was the best combination suitable for the ecological restoration of dump in the Shengli opencast mining area. In addition, the inoculation of AMF affected the colonization of the local soil fungi DSE in plant roots. The colonization intensity of DSE was decreased compared with the natural restoration area after artificial plants planting and inoculation of AMF. The colonization of AMF at the primary roots was higher than the secondary roots. The AMF inoculation reduced the colonization of DSE in the primary roots and improved its colonization in the secondary roots. The AMF and DSE were dominant in the niche of plant primary and secondary roots, respectively. There might be niche competition between AMF and DSE. The total colonization of DSE was significantly positively correlated with soil quality and comprehensive quality index. To a certain extent, the improvement of total colonization of DSE was conducive to the accumulation of nutrients in soil and the improvement of regional comprehensive quality. This study indicates that the incorporation of arbuscular mycorrhizal fungi (AMF) into the ecological rehabilitation of dump in the open-pit mining areas has a positive effect on restoration outcomes. It provides data support for the application of microbial-plant configurations in the reclamation technology for dump.